2013
DOI: 10.1111/cod.12124
|View full text |Cite
|
Sign up to set email alerts
|

Topical botanically derived products: use, skin reactions, and usefulness of patch tests. A multicentre Italian study

Abstract: Contact allergy is a possible adverse effect of natural products. Baseline series supplemented with the commonest botanical allergens may be adequate for detecting most of the cases of contact allergy to natural topical products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 33 publications
1
40
2
2
Order By: Relevance
“…. absorbability rating of the tested cold pressed oils (the best rated oil is indicated) contain a variety of components, whereas patch tests with oil samples may be a reliable source of information [3]. in this study, the patch tests did not prove that the tested oils have high allergic potential; however, it should be mentioned that relatively few people were enrolled in the study, as well as all of them were healthy.…”
Section: Application Studymentioning
confidence: 66%
See 1 more Smart Citation
“…. absorbability rating of the tested cold pressed oils (the best rated oil is indicated) contain a variety of components, whereas patch tests with oil samples may be a reliable source of information [3]. in this study, the patch tests did not prove that the tested oils have high allergic potential; however, it should be mentioned that relatively few people were enrolled in the study, as well as all of them were healthy.…”
Section: Application Studymentioning
confidence: 66%
“…however, it should be noted that natural oils may have some allergic potential due to the admixture of the protein fraction of the plants used to produce cosmetics. the allergic potential of this type of products depends mostly on their purification; however, even highly purified oils may comprise plant allergens [3]. it should be mentioned that commercially available tests with standardized plant allergens may not be representative for detection of most contact allergies due to the fact that natural products Figure 5.…”
Section: Application Studymentioning
confidence: 99%
“…Moreover, in contradiction to the famous conviction regarding the benefits of natural constituents, various reports of side effects experienced have been enumerated by users. 41 According to a study on skin reactions regarding the topical use of botanicals back in 2014, it was reported that contact urticarial, allergic contact dermatitis, adverse response due to photoxicity and irritant contact dermatitis were among the common side effects encountered. 41 Allergic contact dermatitis is the most popular harmful re action reported from the cutaneous application of herbs.…”
Section: Side Effects Of Phytocosmeticsmentioning
confidence: 99%
“…41 According to a study on skin reactions regarding the topical use of botanicals back in 2014, it was reported that contact urticarial, allergic contact dermatitis, adverse response due to photoxicity and irritant contact dermatitis were among the common side effects encountered. 41 Allergic contact dermatitis is the most popular harmful re action reported from the cutaneous application of herbs. 42 Plants and botanicals responsible for these adverse effects are numerous: for example, herbs, seeds, vegetables such as potato and carrot, fruits like tomato, banana, peach and apple, and tea among many others.…”
Section: Side Effects Of Phytocosmeticsmentioning
confidence: 99%
“…Furthermore, despite the popular belief in the harmlessness of natural ingredients, several cases of adverse reactions to plant extracts have been reported, in particular cutaneous side-effects such as allergic contact dermatitis, irritant contact dermatitis, phototoxic reactions, and contact urticaria (Ernst, 2000;Simpson, Law, Storrs, 2004;Corazza et al, 2014). Corazza et al (2014) reported the use of products contanting botanical extracts in 1274 patients (48%)in topical administration; 139 patients (11%) commented on adverse cutaneous reactions; 75 (54%) showed positive reactions with the Italian baseline series.…”
Section: Botanicals and Natural Products In Cosmeticsmentioning
confidence: 99%